Concentric or eccentric physical activity for patients with symptomatic osteoarthritis of the knee: a randomized prospective study. (July 2022) - Trojani, Marie-Charlotte; Chorin, Fréderic; Gerus, Pauline; Breuil, Véronique; Michel, Constance; Guis, Sandrine; Bendahan, David; Roux, Christian
Background: Knee osteoarthritis–related pain limits physical function and leads to functional disability. Physical activity is one of the central recommendations for the management of knee osteoarthritis. Although concentric muscle activities are often preferred to eccentric ones, the corresponding rationale remains controversial. Objective: To explore the effect of a 6-week exercise program on function, pain, and performance in patients with symptomatic knee osteoarthritis. Methods: Patients with symptomatic knee osteoarthritis were included in the prospective EX-ART project (Walking performance in osteoARThritic subjects: effect of an ECCentric muscle strengthening program) and randomized in a 6-week rehabilitation program including either eccentric or concentric activities. Metrics of interest chosen as end points measured before and after the rehabilitation were WOMAC score, pain, and muscular performance (quadriceps power PMAX and contraction strength MMAX ). MRI was also used to assess muscle volume and fat infiltration changes. Results: 30 patients were included in each group; mean age was 74 (±7.6); 69% were women. At week 6, both groups showed a significant improvement in the WOMAC without difference between the two groups ( p  = 0.7). No difference between the two groups was identified for the pain reduction ( p  = 0.7). A significant improvement in the change in PMAX and MMAX at high velocity ( p  = 0.001 and p  = 0.002) was observed in the eccentric group only. A vastus medialis hypertrophy was quantified in the eccentric group only ( p  = 0.002), whereas fat infiltration in the quadriceps muscles was unchanged. Conclusion: Physical activity, whether eccentric or concentric, has a benefit on function and pain in patients with symptomatic knee osteoarthritis. A few differences have been identified between the two types of rehabilitation. More particularly, a gain in muscle performance and vastus medialis volume was found with eccentric rehabilitation only. Registration: www.ClinicalTrials.gov, registration number NCT03167502.